Напівретракції тріоїдів - Жучок, А.В. (Український математичний журнал, 2014)
Определяется и изучается понятие полуретракции триоида. Приведены примеры левых, правых и симметрических полуретракций триоидов. Построены новые теоретико-триоидные конструкции, для которых охарактеризованы некоторые симметрические полуретракции. We introduce and study the notion of semiretraction of trioid. Examples of left, right, and symmetric semiretractions of trioids are given. We also present new theoretical trioid constructions for which some symmetric semiretractions are characterized.